Piloting a Nationally Disseminated, Interactive Human Subjects Protection Program for Community Partners: Unexpected Lessons Learned from the Field. Issue 2 (10th April 2014) - Solomon, Stephanie; Bullock, Sherita; Calhoun, Karen; Crosby, Lori; Eakin, Brenda; Franco, Zeno; Hardwick, Emily; Leinberger‐Jabari, Andrea; Newton, Gail; Odell, Jere; Paberzs, Adam; Spellecy, Ryan
Abstract: Funders, institutions, and research organizations are increasingly recognizing the need for human subjects protections training programs for those engaged in academic research. Current programs tend to be online and directed toward an audience of academic researchers. Research teams now include many nonacademic members, such as community partners, who are less likely to respond to either the method or the content of current online trainings. A team at the CTSA‐supported Michigan Institute for Clinical and Health Research at the University of Michigan developed a pilot human subjects protection training program for community partners that is both locally implemented and adaptable to local contexts, yet nationally consistent and deliverable from a central administrative source. Here, the developers of the program and the collaborators who participated in the pilot across the United States describe 10 important lessons learned that align with four major themes: The distribution of the program, the implementation of the program, the involvement of community engagement in the program, and finally lessons regarding the content of the program. These lessons are relevant to anyone who anticipates developing or improving a training program that is developed in a central location and intended for local implementation.